Genotype of human papilloma virus in invasive cervical carcinoma at Dr. Soetomo Hospital Surabaya - Markus Kore; Gondo Mastutik; Sjahjenny Mustokoweni (Majalah Obstetri dan Ginekologi, 2017)
Objectives: To identify the variants of genotype HPV that most often found in ICC at Dr Soetomo Hospital Surabaya.Materials and Methods: This was an explorative study with cross sectional approach. Specimens used were 30 formalin fix parrafin embedded from squamous cell carcinoma (SCC), adenocarcinoma (AD) dan adenosquamous carcinoma (AS) cervival cancer parients at Dr Soetomo Hospital Surabaya around Januari-Desember 2013, then used for DNA virus extraction and continued for PCR and HPV genotyping.Result : The result of HPV genotyping showed 10 positives from SCC, 6 positives and 4 negatives from AD, and 9 positives and 1 negative from AS. HPV infections in SCC were single infection by HPV 16, 18, 45, 56, and multiple infection by HPV 16+45, in AD were single infection by HPV 16,18, anad multiple infection by HPVhr+hr 68b+72 and HPVlr+hr  6+18+45, and in AS were single infection by HPVhr 16, 18, 45 and mutiple infection by HPV lr+hr 6+59.Conclusion : Infections HPV in ICC were single infection by HPV16, 18, 45, 56 and mutiple infection by HPV16+45, 68b+72, 6+18+45, 6+59. HPV 18 has highest prevalence in ICC patient from Dr Soetomo Hospital, followed by HPV16, 6, 45, 56, 59.